2012
DOI: 10.1071/an11280
|View full text |Cite
|
Sign up to set email alerts
|

The level of tree legumes required to meet the maintenance energy requirements of Ongole (Bos indicus) cows fed rice straw in Indonesia

Abstract: Improving the productivity and profitability of smallholder cattle enterprises in Indonesia requires greater and more efficient utilisation of underutilised feed resources such as rice straw. The experiment tested the hypothesis that an Ongole cow with low energy requirements can maintain weight (W) on a rice straw-based diet with the addition of a small amount of tree legumes. Thirty-two Ongole cross (Bos indicus) cows were allocated to one of four treatments in a randomised block design with eight cows per t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…It is not unreasonable to suggest that feeding legume hay to cows to maintain, or even increase, LW during periods of nutritional stress will contribute to improvements in conception rates and shorter inter-calving intervals. Our results provide an on-farm validation of previous pen-feeding studies showing that small amounts of legumes provide sufficient energy and CP for maintenance of LW of cows fed otherwise low-quality diets (Syahniar et al 2012;Antari et al 2014aAntari et al , 2014b. Higher levels of supplementation may be required to maintain condition of cows during periods of higher energy demands, such as late gestation and early lactation, but could play an important role in reducing loss of condition during those times.…”
Section: Prospects For Improving Livestock Productivity In Eastern Insupporting
confidence: 83%
See 1 more Smart Citation
“…It is not unreasonable to suggest that feeding legume hay to cows to maintain, or even increase, LW during periods of nutritional stress will contribute to improvements in conception rates and shorter inter-calving intervals. Our results provide an on-farm validation of previous pen-feeding studies showing that small amounts of legumes provide sufficient energy and CP for maintenance of LW of cows fed otherwise low-quality diets (Syahniar et al 2012;Antari et al 2014aAntari et al , 2014b. Higher levels of supplementation may be required to maintain condition of cows during periods of higher energy demands, such as late gestation and early lactation, but could play an important role in reducing loss of condition during those times.…”
Section: Prospects For Improving Livestock Productivity In Eastern Insupporting
confidence: 83%
“…Between August and November (14 weeks), all cows grazed together during the day as part of the larger herd and were penned at night in communal pens. Cows that received the legume supplement were penned as a separate group and were fed dried clitoria hay daily at~10 g dry matter (DM)/kg LW, which was estimated to be adequate for maintenance of LW based on the energy requirements of Ongole cows (Syahniar et al 2012;Antari et al 2014b). Cows in the control group did not receive any feed overnight, which is standard practice for farms in this region.…”
Section: Methodsmentioning
confidence: 99%
“…No significant difference was found for DMI: kg/d (P >0.05) when the ratio of BHM in the concentrate increased. No differences in total feed intake were found in Ongole cross (Bos indicus) cows (318 ± 12 kg LW) fed rice straw ad libitum with supplemented four levels of legumes (Gliricidia sepium and Leucaena leucocephala) (0, 11, 21, and 42 g DM/kgW 0.75 day) for 20 weeks (Syahniar et al, 2012). Similarly, Antari et al (2014) reported that there was no significant differences in total DM and ME intake or rice straw intake between mature Brahman (Bos indicus) cows fed on two different diets of fed rice straw and onggok plus urea or gliricidia in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Most cattle in East Java are fed diets based on crop residues and agricultural byproducts such as rice straw (Hanifah et al, 2010). Rice straw is low in organic matter digestibility (OMD, 51%) and crude protein (CP, 5% DM), but can be used to maintain cow liveweight (Syahniar et al, 2012). However, the feeding Dian Ratnawati et al/Animal Production.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, small amounts of high-quality supplements, such as rice bran or tree legumes, can be used to supply shortfalls in energy and/or CP from rice straw. Syahniar et al (2012) found that untreated rice straw can maintain weight and Body Condition Score (BCS) of Ongole cows when supplemented with tree legumes at the level of 2.8 g DM/kg W/d.…”
Section: Introductionmentioning
confidence: 99%